First measurement of the ratio B(t --> Wb)/B(t --> Wq) and associated limit on the Cabibbo-Kobayashi-Maskawa element /V(tb)/. - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amendolia, SR; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Asakawa, T; et al. (2001)
We present the first measurement of the ratio of branching fractions R identical withB(t-->Wb)/B(t-->Wq) from p_p collisions at sqrt[s] = 1.8 TeV. The data set corresponds to 109 pb(-1) of data recorded by the Collider Detector at Fermilab during the 1992-95 Tevatron run. We measure R = 0.94(+0.31)(-0.24)(stat+syst) or R>0.61 (0.56) at 90% (95)% C.L., in agreement with the standard model predictions. This measurement yields a limit on the Cabibbo-Kobayashi-Maskawa quark mixing matrix element /V(tb)/ under the assumption of three generations and unitarity.